2018
DOI: 10.1002/pca.2803
|View full text |Cite
|
Sign up to set email alerts
|

Semi‐preparative isolation and purification of phenolic compounds from Achyrocline satureioides (Lam) D.C. by high‐performance counter‐current chromatography

Abstract: Introduction Phenolic compounds present in Achyrocline satureioides are known to have therapeutic benefits like antioxidant, anti‐inflammatory, and antitumour properties. The main polyphenols present in the plant are quercetin (QCT), luteolin (LUT), 3‐O‐methylquercetin (3OMQ), and achyrobichalcone (ACB). However, the effective isolation and purification of these compounds from A. satureioides inflorescences are not an easy task. Objective To develop an efficient high‐performance counter‐current chromatography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…These biological properties have been very often ascribed to the high content of phenolic constituents in the inflorescences. Thus, the extraction and isolation of the flavonoids QCT, LUT, and 3OMQ has been the goal of many studies [2,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…These biological properties have been very often ascribed to the high content of phenolic constituents in the inflorescences. Thus, the extraction and isolation of the flavonoids QCT, LUT, and 3OMQ has been the goal of many studies [2,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…3OMQ is the most abundant among the flavonoids-aglycones in the cultivated species. 5 ACB is a novel molecule, reported only for A. satureioides, with a similar structure to other natural bichalcones. [6][7][8] 3OMQ possess biological properties and, in particular, has cytotoxic effects against the breast cancer cell lines SK-BR-3 and MCF-7, including drug-resistant strains.…”
Section: Introductionmentioning
confidence: 91%
“…The separation and isolation of ACB and 3OMQ from the dry extract was performed as previously described, using high-performance countercurrent chromatography (HPCCC, Dynamic Extraction). 5 The instrument was equipped with polytetrafluoroethylene (PTFE) bobbins with 1.6 mm inner diameter of tubing, 136 ml total volume and 6 ml sample loop. The solvent was pumped into the column with isocratic pumps (Scientific Systems, Inc., PA) at a flow rate of 6.0 ml/min while the apparatus was run at a rotation speed of 1,600 rpm.…”
Section: Plant Material Extraction and Isolationmentioning
confidence: 99%
“…Generally, a suitable composition for the twophase solvent system is crucial for a perfect HSCCC separation, which relied on satisfactory partition coefficient (K D ) values ranging from 0.5 to 2.0 for the target components. 25,26 Previous studies have identified the flavonoids from the thorns of G. sinensis mainly as flavonoid aglycones as well as a few flavonoid glycosides. Thus, several solvent systems of n-hexane-ethyl acetatemethanol-water, n-hexane-ethyl acetate-n-butanol-water, chloroform-methanol-water, dichloromethane-methanol-water, and dichloromethane-methanol-n-butanol-water with different composition ratios, were applied for testing the K D values of the five main constituents (1)(2)(3)(4)(5) in the DES extracts (Table 2).…”
Section: Optimisation Of Two-phase Solvent Systems For Des Extracted Flavonoids By Hscccmentioning
confidence: 99%